Anaphorical Use of Person Deixis in Japanese - Midori, Fukuhara (Journal of Modern Languages, 2017)
This study considers the problems of Malaysian students who learn Japanese, regardless of whether their first language is Malay, Chinese or English in its difficulty to re-refer to a person who has previously been mentioned, i.e. the third person. Japanese is one of those languages that do not have third person pronouns. The paper’s treatment is restricted to the third person singular.